PENGARUH MODEL MISSOURI MATHEMATICS PROJECT DALAM PEMBELAJARAN MATEMATIKA TERHADAP KETUNTASAN HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG TABUNG - Yakobus Ason (STKIP Melawi, 2014)
Abstract: The general objective of this research is to know the results of student learning on the material tube room wake up when compared to the results of the ketuntasan study after they are taught using MMP in class IX Junior High Nanga Pinoh Budi County Faithful Melawi. In detail the purpose of the research was to determine: (1) student learning outcomes. the difference in the materials up the space tube if compared between Ketuntasan and Posttest results study.(2) differences in student learning outcome on that matter up space tube if compared between the delayed test results ketuntasan and learn. (3) the activity of the students attend the learning material on MMP model using up space tubes for students of class IX JUNIOR Loyal Budi Nanga Pinoh Melawi Regency. This research uses experimental methods with Pre-experimental design. The design used is the One-Shot Case Study. The population in this research is the entire Junior class IX students loyal to Nanga Pinoh Melawi Regency Budi that consists of one class of 20 students. The technique used is the sample determination of sampling is saturated. Data collecting techniques and tools to ketuntasan using a tool with measurement techniques post-test and Delayed test, using the technique of direct observation activity with the tool in the form of sheets of observation activities, teachers and students. Data processing of the results obtained; the average results of student learning test after being given the post instruction using model Missouri Mathematict Project is the 85,51, and the average results of student learning test delayed was 81.60, students are very active during the follow up on that matter learning space tube by using model Missouri Mathematict Project. Key words: model missouri mathematics project, the learning of mathematics,Abstrak: Tujuan umum dalam penelitian ini adalah untuk mengetahui hasil belajar siswa pada materi bangun ruang tabung jika dibandingkan dengan ketuntasan hasil belajar setelah mereka diajarkan menggunakan MMP di kelas IX SMP Setia Budi Nanga Pinoh Kabupaten Melawi. Secara rinci tujuan penelitian adalah untuk mengetahui: (1) Perbedaan hasil belajar siswa pada materi bangun ruang tabung jika dibandingan antara posttest dan ketuntasan hasil belajar; (2) Perbedaan hasil belajar siswa pada materi bangun ruang tabung jika dibandingan antara delayed test dan ketuntasan hasil belajar; (3) Aktivitas siswa selama mengikuti pembelajaran menggunakan model MMP pada materi bangun ruang tabung bagi siswa kelas IX SMP Setia Budi Nanga Pinoh Kabupaten Melawi. Penelitian ini menggunakan metode eksperimen dengan bentuk pre-eksperimental design. Rancangan yang digunakan adalah One-Shot Case Study. Populasi dalam penelitian ini adalah seluruh siswa kelas IX SMP Setia Budi Nanga Pinoh Kabupaten Melawi yang terdiri dari satu kelas yang berjumlah 20 siswa. Teknik penentuan sampel yang digunakan adalah sampling jenuh. Teknik dan alat pengumpul data untuk ketuntasan menggunakan teknik pengukuran dengan alat berupa post-test dan Delayed test, aktivitas menggunakan teknik observasi langsung dengan alat berupa lembar pengamatan aktivitas guru dan siswa. Dari hasil pengolahan data diperoleh; rata-rata hasil belajar siswa post test setelah diberikan pembelajaran menggunakan model Missouri Mathematict Project adalah 85,51, dan rata-rata hasil belajar siswa delayed test adalah 81.60, siswa sangat aktif selama mengikuti pembelajaran pada materi bangun ruang tabung dengan menggunakan model Missouri Mathematict Project.Kata Kunci: model missouri mathematics project, pembelajaran Matematika, ketuntasan hasil belajar siswa.